Impacts of Policy and Price Changes on Sugarcane Production in Central Part of Thailand - Potchanasin, Chakrit; Athipanyakul, Thanaporn; Nantajit, Chompunuch (Journal of Applied Economics and Management Strategy, 2023)
This paper aimed to compare cost benefit of sugarcane and others alternative crops including rice, maize, and cassava, and analyze impact from policy and price changes affecting sugarcane production. The study used interviewing with the questionnaire to collect 824 samples from the farmers in Kanchanaburi and Supanburi provinces. Also, this study had analyzed changes in planted area by applying Positive Mathematical Programming model. The results show that sugarcane production generated more profit than other alternative crops. Implementing policies of transport regulation and sugarcane burning harvest regulation will increase cost of sugarcane production and it will induce reduction of sugarcane planted area by 2.05 and 0.94 percent, respectively. For sugarcane prices, the results showed that sugarcane price would be negatively by 5.4 percent while, in contrast, cassava price has positive impact by 29 percent. Therefore, under this situation, sugarcane planted area would decrease by 8.21 percent. To cope with reduction of sugarcane production, the stakeholders should handle lower sugarcane production e.g. improving sugar logistic efficiency, developing of green sugarcane harvesting equipment, and doing contract farming with the farmers.